2000
DOI: 10.1063/1.481106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the gas–liquid critical point from the second virial coefficient

Abstract: We show that whereas the critical point is very sensitive to the range of interaction, the second virial coefficient has a fairly constant value at the critical temperature. This enables us to predict the critical temperature with fair accuracy. We discuss the connection between the second virial coefficient as a predictor for the critical temperature and the second virial coefficient as predictor in crystal growth as was proposed by George and Wilson ͓A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
262
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(293 citation statements)
references
References 62 publications
29
262
2
Order By: Relevance
“…When B 2 becomes sufficiently negative a colloidal suspension becomes unstable. 47 In Fig. 10 we plotted B 2 as a function of the relative polymer concentration for four colloid-polymer size ratios.…”
Section: Fig 8 Interaction Potential Between Two Spheres Immersed Imentioning
confidence: 99%
“…When B 2 becomes sufficiently negative a colloidal suspension becomes unstable. 47 In Fig. 10 we plotted B 2 as a function of the relative polymer concentration for four colloid-polymer size ratios.…”
Section: Fig 8 Interaction Potential Between Two Spheres Immersed Imentioning
confidence: 99%
“…Such virial coefficients are very sensitive to the strength and nature of the depletion interaction 28 . A recent study 67 has shown that for many simple systems consisting of a HS like repulsion with an additional attractive potential, the location of the liquid-gas or fluid-fluid critical point can be correlated with the point where the reduced virial coefficient…”
Section: Second Virial Coefficients Phase-diagramsmentioning
confidence: 99%
“…To estimate whether this deviation has a significant effect on the computed phase behavior, we calculate the normalized second virial coefficients B * 2 for both fitted and measured potentials for system 2. According to Noro and Frenkel's extended principle of corresponding states, the second virial coefficient is a rough estimator of the phase behavior that should arise from a given potential: 34,35 a B * 2 that is positive correlates with net repulsion between the particles, indicating that a phase transition should not occur; a B * 2 that is close to zero indicates little net attraction or repulsion between the particles, so a phase transition is not expected. Phase transitions are expected to occur when B * 2 becomes smaller than −1.5.…”
Section: B Potential Modelmentioning
confidence: 99%